The Ecuadorian oil boom of the 1970s: Economic Policy and Its Historical Legacy - de la Torre, Augusto (Revolutionary nationalism: The 1970s and the Contemporary History of Ecuador, 2026)
He analyzes three critical legacies of the oil boom that continue to weigh on the national economy: the macroeconomic boom-and-bust cycle, the fuel subsidy trap, and the “resource curse.” The author argues that the boom fostered habits of excessive public spending and debt that were repeated in the 2000s. Furthermore, he criticizes the import substitution model for creating an inefficient industry dependent on state foreign exchange.